Nationwide Turkish Cohort Study of Hypophosphatemic Rickets - Siklar, Zeynep; Turan, Serap; Bereket, Abdullah; Bas, Firdevs; Guran, Tulay; Akberzade, Azad; Berberoglu, Merih (Galenos Yayincilik, 2020)
Objective: Hypophosphatemic rickets (HR) is a rare renal phosphate-wasting disorder, which is usually X-linked and is commonly caused by PHEX mutations. The treatment and follow-up of HR is challenging due to imperfect treatment options. Methods: Here we present nationwide initial and follow-up data on HR. Results: From 24 centers, 166 patients were included in the study. Genetic analysis (n = 75) showed PHEX mutation in 80% of patients. The mean follow-up period was 6.7 +/- 2.4 years. During the first 3-years of treatment (n = 91), mild increase in phosphate, decrease in alkaline phosphatase and elevation in parathyroid hormone (PTH) levels were detected. The height standard deviation scores were -2.38, -2.77, -2.72, -2.47 at initial, 1st, 2nd and 3rd year of treatment, respectively (p > 0.05). On follow-up 36% of the patients showed complete or significant improvement in leg deformities and these patients had similar phosphate levels at presentation with better levels in 1st and 2nd years of treatment; even the treatment doses of phosphate were similar. Furthermore, 27 patients developed nephrocalcinosis (NC), the patients showed no difference in biochemical differences at presentation and follow-up, but 3rd year Pill was higher. However, higher treatment doses of phosphate and calcitriol were Found in the NC group. Conclusion: HR treatment and follow-up is challenging and our results showed higher treatment doses were associated with NC without any change in serum phosphate levels, suggesting that giving higher doses led to increased phosphaturia, probably through stimulation of fibroblast growth factor 23. However, higher calcitriol doses could improve bone deformities. Safer and more efficacious therapies are needed.
Keywords: Hypophosphatemic rickets; PHEX; treatment